The way forward for livestock and the environment - Herrero, Mario; Thornton, Philip K.; Gerber, Pierre J.; Zijpp, A.J. van der; Steeg, Jeannette van de; Notenbaert, An Maria Omer; Lecomte, P.; Tarawali, Shirley A.; Grace, Delia (University of the Free State and CTA, 2010)
Livestock provide many benefits to society, but at the same time, they generate considerable pressure on land, water and biomass resources and are responsible for 18 percent of total greenhouse gas emissions. The total demand for livestock products may almost double by 2050, mostly in the developing world due to increases in population density, urbanisation and incomes. At the same time, existing trade-offs and competing demands for natural resources with other sectors will intensify, making it necessary to take a combination of measures to reduce the environmental footprint of livestock production. Measures such as sustainable intensification of crop-livestock systems, payments for ecosystem services, income diversification in pastoral systems, regulation of industrial systems and livestock-product demand management could play a significant role in ensuring sustainable livestock production, livelihoods and environmental protection. This chapter examines the main environmental interactions of livestock production and suggests ways to improve them.